Avançar no estado democrático de direito: a participação política na democracia brasileira - Sales, Dimitri Nascimento (2007)
The Brazilian history does not have an extensive democratic experience. Still, in 10/05/1998, the Country has enacted a Constitution which conveys a clear improvement towards the democracy, in our country. It has adopted, for the first time in history, the semi-democratic type of government as a source of state legitimacy. In that sense, the Constitution appoints the democratic ways by which the population will reach a decision. This essay will discuss if the participatory model adopted by the Brazilian Constitution is comprehensive; that is to say, if it conveys all the means by which the State obtains legitimacy. Moreover, it will discuss if it is necessary to create new instruments of popular participation and, also, how could the instruments already existing be implemented, in order to enhance and propitiate the establishment of a public space, in which all the democratic agents would be able to express their voices. In order to accomplish such task, it will be necessary to study the concept of democracy that can, effectively, implement the substantive ideal of Democratic Rule of Law. Moreover, different conceptions of democracy will be studied so that the peculiar constituents of the semi-direct democracy can be thoroughly analyzed. In this process, the statute concerning the subject will be also studied. At the end, the essay will suggest new instruments by which the popular participation can be improved. The result of all this questionings was due to the acknowledgment that the extension of de public space that can include citizens in the decisionmaking process is a necessary condition for the enhancement of the Democratic Rule of Law